2018
DOI: 10.1038/gim.2017.92
|View full text |Cite
|
Sign up to set email alerts
|

Survival trends from the Prader–Willi Syndrome Association (USA) 40-year mortality survey

Abstract: Background Prader-Willi syndrome (PWS) is a complex genetic disorder characterized by hyperphagia and morbid obesity with increased cardiopulmonary and hyperphagia-related mortality. Survival trends in PWS were evaluated to assess the impact of modern interventions on mortality risk. Methods The PWSA (USA) 40-year mortality syndrome-specific database of 486 death reports was utilized to examine survival trends in PWS and cohort effects for recent deaths (years 2000–2015, N=331) relative to deaths prior to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 85 publications
(47 citation statements)
references
References 29 publications
1
46
0
Order By: Relevance
“…b The average BMI was low for an obesity syndrome as 56% of our PWS participants were less than 12 years of age. 1.0 (0.4, 2.2) 2.4 (0.0, 13.1) mortality database Manzardo et al, 2017). Our study of the mortality incidence rate in PWS per 100 years of exposure is novel and showed a low rate, not significantly different than that observed in the EMO group.…”
Section: Resultsmentioning
confidence: 53%
“…b The average BMI was low for an obesity syndrome as 56% of our PWS participants were less than 12 years of age. 1.0 (0.4, 2.2) 2.4 (0.0, 13.1) mortality database Manzardo et al, 2017). Our study of the mortality incidence rate in PWS per 100 years of exposure is novel and showed a low rate, not significantly different than that observed in the EMO group.…”
Section: Resultsmentioning
confidence: 53%
“…Children with PWS are at high risk for mortality from respiratory infections. This risk is likely due to their hypotonia and inability to adequately cough to clear respiratory secretions [8]. Our survey showed that receiving the Synagis vaccine was associated with a lower incidence of contracting RSV, whereas those who were unable to get the vaccine had a significantly higher risk of contracting the virus.…”
Section: Discussionmentioning
confidence: 73%
“…Respiratory infections were the primary cause of death for children with PWS <1 year of age and account for 50% of deaths for children less than 2 years of age [6]. Multiple studies have confirmed that respiratory failure/infections are a common cause of mortality in young children with PWS [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In summary, the ultimate goal is to change the face of PWS by early identification and awareness which will permit proactive monitoring of the diet, and exercise and treatment with growth hormone at an early age thus preventing co‐morbidities associated with PWS and reducing the current high mortality rate (Butler et al, ; Manzardo et al, ). The methylation testing used for diagnosis of PWS would also have the added benefit of detecting Angelman syndrome (AS).…”
Section: Discussionmentioning
confidence: 99%